MINAT BERKARIER DI INDUSTRI PERHOTELAN DIPENGARUHI OLEH PENGALAMAN MAGANG - Nurul Sukma Lestari; Evi Millenia (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of internship experience on interest in a career in the hotel industry. The population of this study were students of the XYZ hotel school. The method used is quantitative using SPSS for data processing. Data were collected by distributing questionnaires randomly. The sampling technique used in this study is a non-probability sampling technique with a quota sampling technique. In this study analyze the correlation, coefficient of determination and Simple Linear Regression to examine the effect and answer the hypothesis in this study. The result of this research is Internship Experience has a significant effect on Career Interest. The researcher suggests that universities expand their relationship with industry so that suitable internships are available for students to develop their skills, so that it will lead to self-confidence for a career in the hotel industry